2011
DOI: 10.1158/1078-0432.ccr-11-0050
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor Receptors Are Components of Autocrine Signaling Networks in Head and Neck Squamous Cell Carcinoma Cells

Abstract: Purpose We previously reported that a fibroblast growth factor (FGF) receptor (FGFR) signaling pathway drives growth of lung cancer cell lines of squamous and large cell histologies. Herein, we explored FGFR dependency in cell lines derived from the tobacco-related malignancy, head and neck squamous cell carcinoma (HNSCC). Experimental Design FGF and FGFR mRNA and protein expression was assessed in nine HNSCC cell lines. Dependence on secreted FGF2 for cell growth was tested with FP-1039, an FGFR1-Fc fusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
81
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 48 publications
11
81
0
1
Order By: Relevance
“…Several different mAb have been developed to target components of the FGF-FGFR axis: GP369 (Bai et al, 2010), GAL-FR21 (Zhao et al, 2010), GAL-FR22 (Inokuchi et al, 2015), GAL-F2 , MFGR1877S (Fauvel and Yasri, 2014), hLD1.vb (Bumbaca et al, 2011), FP-1039(Marshall et al, 2011, R3Mab (French et al, 2012), PRO-001 (French et al, 2012), 1A6 (Pai et al, 2008) and LD1 (French et al, 2012). Two main mechanisms of action have been considered; either blocking ligand binding (trap-ligand) or preventing receptor dimerization.…”
Section: Antibodies Against Fgfs and Fgfrs And Fgf-ligand Trapmentioning
confidence: 99%
“…Several different mAb have been developed to target components of the FGF-FGFR axis: GP369 (Bai et al, 2010), GAL-FR21 (Zhao et al, 2010), GAL-FR22 (Inokuchi et al, 2015), GAL-F2 , MFGR1877S (Fauvel and Yasri, 2014), hLD1.vb (Bumbaca et al, 2011), FP-1039(Marshall et al, 2011, R3Mab (French et al, 2012), PRO-001 (French et al, 2012), 1A6 (Pai et al, 2008) and LD1 (French et al, 2012). Two main mechanisms of action have been considered; either blocking ligand binding (trap-ligand) or preventing receptor dimerization.…”
Section: Antibodies Against Fgfs and Fgfrs And Fgf-ligand Trapmentioning
confidence: 99%
“…CONCERT-1; NCT00547157), are also underway. High expression of fibroblast growth factor receptors (FGFRs) have been identified in SCCHN [83,84], and demonstrated to be associated with poor clinical outcome [84], thus identifying FGFR as another potential therapeutic target in patients with SCCHN. Targeting AKT and MEK, downstream effectors of the PI3K/AKT and MAPK pathways, respectively, in combination may provide a molecular therapeutic target for RAS-driven tumorigenesis in oral cancer [85].…”
Section: Blocking Pi3k Pathway and Other Pathways Concurrentlymentioning
confidence: 99%
“…Similar results were obtained for human head and neck squamous carcinoma cell lines. Indeed, FGF2 and FGFR coexpression frequently occurs in these cells, leading to an autocrine loop of stimulation that may involve also EGFR activation [77]. Several FGFs, including FGF1, FGF2, FGF5, FGF6, FGF7, FGF8, FGF9, FGF10, FGF17, FGF18 and FGF19 are upregulated in human prostate cancer [38] and murine studies have demonstrated the complex FGF/FGFR-dependent interplay between the epithelial and mesenchymal compartments in these tumors [78].…”
Section: Aberrant Autocrine and Paracrine Ligand Signallingmentioning
confidence: 99%